Caregiver perceptions of a pediatric produce prescription program during the COVID-19 pandemic - Li, Zhongyu; Zhang, Fang Fang; Cash, Sean B.; Hager, Kurt; Trevino, Leo; Folta, Sara C. (Frontiers in Nutrition, 2024)
Introduction: Produce prescription programs are rapidly expanding as a type of Food is Medicine intervention with prospects for mitigating food insecurity and reducing diet-related health disparities. Gaining insight into participant perspectives on program logistics and perceived impacts is crucial to program success and improvements.Between May -June 2021, we conducted individual and small group interviews with 23 caregivers with children aged 1-5 years who participated in a produce prescription program from 2020 to 2021 in Texas, U.S. They were provided with a gift card to a major national grocery retailer to purchase fresh produce. The card was reloaded $60 monthly for eight months with automatic rollover of unused funds to the next month. Participants also received nutrition education in the form of two videos. A deductive analysis approach was employed, and NVivo qualitative data analysis software was used to perform coding and to assist with subsequent analyses.Results: All 23 participants were female, with an average age of 37.5 years, and the majority identified as Hispanic/Latino (83%). About 43% of the families had three or more children. Six themes were generated from interviews. Three of these themes were related to program logistics: 1) ease of program use; 2) participant satisfaction with the incentive; and 3) desire for additional store options. The remaining main themes pertained to program impact: 1) the enhanced ability to purchase produce; 2) the usefulness of the nutrition education; and 3) persistent challenges encountered when preparing the produce for picky eaters and young children.A pediatric produce prescription program was perceived as logistically easy and a helpful source of financial support for accessing fresh produce. Program features such as card-based incentive system and partnership with major grocery retailer were favored by participants. For future program design, it may be beneficial to consider collaborating with multiple grocery outlets and enhancing the intensity and targeting of nutrition education.